Association between IL-15 and insulin plasmatic concentrations in patients with pulmonary tuberculosis and type 2 diabetes. (July 2018) - Sánchez-Jiménez, Roberto; Cerón, Eduarda; Bernal-Alcántara, Demetrio; Castillejos-López, Manuel; Gonzalez-Trujano, Eva; Negrete-García, Maria Cristina; Alvarado-Vásquez, Noé
Abstract: IL-15 is part of the immune response in pulmonary tuberculosis (PTB) but amazingly, it may also induce physiological effects similar to those of insulin. We evaluated the IL-15 and insulin plasmatic levels in adults with PTB and with or without type 2 diabetes mellitus (DM2), who received previous antituberculosis therapy for at least 2 months. We analyzed the concentrations of glucose, glycated hemoglobin, insulin, as well as levels of IL-15, IL-2, IFN-γ, and TNF-α in patients with PTB, patients with PTB-DM2, household contacts with DM2 (C-DM2), and healthy household contacts (H-C). Our results showed unexpected high levels of glucose, insulin, and IL-15 in the PTB and C-DM2 groups. In comparison, low levels of these same indicators were observed in the PTB-DM2 and H-C groups. Interestingly, our analysis showed a positive correlation of IL-15 with insulin in the PTB group (r = 0.73) and in the C-DM2 group (r = 0.66). In comparison, a weak correlation between IL-15 and insulin was observed in the PTB-DM group (r = 0.10) and in the H-C group (ρ = 0.26). Our results suggest an association between IL-15 and insulin levels in the patient with PTB. Intriguingly, this association was weaker in the patient with PTB-DM2.